The Value of Circulating Tumor HPV DNA in Head and Neck Squamous Cell Cancer: A Review - Dok, Rüveyda; Nuyts, Sandra; Lopez, Fernando; Bradford, Carol; Forastiere, Arlene A.; Strojan, Primož; Agaimy, Abbas; Stenman, Göran; Mariano, Fernanda V.; Leivo, Ilmo; Rao, Karthik N.; Williams, Michelle; et al. (MDPI, 2026)
Human papillomavirus (HPV)-related oropharyngeal squamous cell carcinomas (OPSCC) represent a distinct subgroup of head and neck squamous cell carcinoma (HNSCC) characterized by better prognosis and increased radiosensitivity compared to HPV-negative OPSCC. However, current diagnostic and monitoring methods, including tissue biopsies and imaging, are insufficient for precise risk stratification and early detection of recurrence, leading to challenges in treatment de-escalation and surveillance strategies. Circulating tumor HPV DNA (ctHPV-DNA) has emerged as a promising minimally invasive biomarker that offers tumor-specific detection and monitoring capabilities, potentially transforming the management of HPV-related OPSCC through early disease detection, treatment response assessment, recurrence surveillance stratification, and disease monitoring. Despite encouraging results from early clinical studies, current use is limited to trial settings. Large-scale prospective studies are needed to validate its clinical utility and determine whether early ctHPV-DNA testing can improve patient outcome while reducing treatment related morbidity. This review outlines the biological rationale, technological approaches, and current clinical evidence for ctHPV-DNA in HPV-related OPSCC, emphasizing its potential role in treatment monitoring and surveillance.